The Value of Bank Capital and the Structure of the Banking Industry - Allen, Franklin; Fulghieri, Paolo; Mehran, Hamid (Review of Financial Studies, 2011)
The critical role played by financial institutions in the recent financial crises has generated renewed interest on the corporate finance of the banking firm and the impact of the banking sector on the real economy. This paper introduces the special issue of the Review of Financial Studies dedicated to “The Value of Bank Capital and the Structure of the Banking Industry.” The special issue combines papers presented at the conference on “Corporate Finance of Financial Intermediaries” in September 2006, which was jointly organized by the Federal Reserve Bank of New York, the Wharton Financial Institutions Center of the University of Pennsylvania, and the Review of Financial Studies, with other related papers.